2009
DOI: 10.1080/00071660903391709
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of mutations in ADSL and GARS-AIRS-GART genes on IMP content in chickens

Abstract: 1. The objective of this study was to investigate the effect of ADSL gene, GARS-AIRS-GART gene and their combination genotype on inosine monophosphate content (IMP) in chicken. 2. The chicken breeds used for this study were Recessive White chicken (RW, Jiang-13 strain of white Plymouth Rock) and preserved population of 4 Chinese native chicken breeds, including Silkies, Baier, Tibetan and Xiaoshan. 3. The primers for exon 2 in ADSL gene and 5'UTR region in GARS-AIRS-GART gene were designed and the single nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…In agreement with Shu et al (2007b), individuals inheriting EE (or MM) genotypes at the ADSL (or GARS-AIRS-GART) genes had significantly higher IMP content in breast muscle than did those inheriting FF (or NN) genotypes. In the present study, there was no significant difference in IMP between EE and EF, nor between MM and MN genotypes.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In agreement with Shu et al (2007b), individuals inheriting EE (or MM) genotypes at the ADSL (or GARS-AIRS-GART) genes had significantly higher IMP content in breast muscle than did those inheriting FF (or NN) genotypes. In the present study, there was no significant difference in IMP between EE and EF, nor between MM and MN genotypes.…”
Section: Discussionsupporting
confidence: 76%
“…The products of the ADSL (adenylosuccinate lyase deficiency) gene and the GARS-AIRS-GART (glycinamide ribonucleotide synthetaseaminoimidazole ribonucleotide synthetase-glycinamide ribonucleotide transformylase) gene are two key enzymes that are involved in the synthesis of IMP. Chicken ADSL and GARS-AIRS-GART genes have been studied as candidate genes for the effects on the IMP content in muscle (Shu et al, 2007b) and favourable association between genotypes and higher IMP content has been demonstrated in several Chinese native chicken breeds. Beijing-you (BJY) is a Chinese local chicken breed with a history of nearly 300 years.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that ADSL and GARS-AIRS-GART affect IMP content in chickens (Shu et al, 2009;Ye et al, 2010). In this study, ADSL and GARS-AIRS-GART had high expression levels in LL and low expression levels in heart and liver.…”
Section: Effect Of Different Tissues On Gene Expressionmentioning
confidence: 65%
“…ADSL and GARS-AIRS-GART are enzymes involved in the biosynthesis of purine nucleotides, which contribute to delicate flavors in muscle tissue (Kan and Moran, 1995;Shu et al, 2009). Recent studies have reported that ADSL and GARS-AIRS-GART affect IMP content in chickens (Shu et al, 2009;Ye et al, 2010).…”
Section: Effect Of Different Tissues On Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation